Penerapan Manajemen Konflik Mengenai Peran Pemerintah Desa Sidomulyo Dalam Mengatasi Diskriminasi Antara Etnis Madura Dan Etnis Jawa - Nadhir, Muhammad Ulin; Azmi, Miqdad Akmalul; Setiawan, Kabul Budi; Zuhro’ Fitriana, Ani Qotus (CV. ITTC INDONESIA, 2023)
Discrimination is the act of disadvantaging or disregarding certain people or groups based on their characteristics such as ethnicity. Discrimination can result in injustice, inequality and oppression of certain people or groups, and can exacerbate existing social problems. Based on this phenomenon, it is a priority for the Sidomulyo Village Government to overcome discrimination so that people live in peace. This study aims to describe the application of conflict management in overcoming discrimination by the Madurese tribe against the Javanese tribe in Sidomulyo Village. This research uses a qualitative approach and case study research type. Data collection is by observation, interview, and documentation. The data analysis carried out is data reduction, data presentation and conclusions. This study found the conclusion that the application of conflict management regarding the role of the Village Government in overcoming conflicts of discrimination between the Madurese and Javanese can be done with steps such as (1) understanding the problem, (2) holding a dialog, (3) finding solutions, (4) taking appropriate action, (5) evaluating.